Can Extra Daytime Light Exposure Improve Well-Being and Sleep? A Pilot Study of Patients With Glaucoma - Kawasaki, Aki; Udry, Morgane; El Wardani, Mohamad; Münch, Mirjam (Frontiers in Neurology, 2021)
Glaucoma damages retinal ganglion cells, including intrinsically photosensitive retinal ganglion cells (ipRGCs). These cells modulate various non-visual physiological and psychological functions which are modulated by light. In patients with glaucoma, we assessed the effect of daily bright light exposure (LE) on several melanopsin-dependent functions, such as the pupil constriction, circadian rest-activity cycles, sleep and subjective wellbeing including relaxation, alertness and mood. Twenty patients participated in the study (9 women, 11 men, mean age = 67.6 ± 7.5 y). Pupillometry was performed before the LE weeks and repeated on the last day of LE. The post-illumination pupil response (PIPR) was calculated as a proxy for melanopsin-dependent activation. Participants continuously wore an activity monitor and self-assessed sleep quality, wellbeing and visual comfort for 7 days before and during 4 weeks of daily bright LE (30 min to 10,000 lux polychromatic bright white light). After the LE, there was a significantly greater PIPR and higher subjective sleep quality when compared to the pre-LE week (p < 0.05), but no significant changes in 24-h rhythms or sleep parameters. A greater PIPR was correlated with an increase in circadian amplitude and higher inter-daily stability (derived from rest-activity cycles; p< 0.05). In a small group of patients with glaucoma, scheduled daily bright light exposure could improve subjective sleep quality. These findings highlight the importance to evaluate and maintain non-visual functions at different levels in patients with progressive loss of ipRGCs.